Circulating mucosal-like IgA responses increase with severity of Puumala orthohantavirus-caused hemorrhagic fever with renal syndrome - Cabrera, Luz E.; Buckner, Cienna; Then, Veronica; Mäki, Sanna; Vapalahti, Olli; Vaheri, Antti; Hepojoki, Jussi; Tietäväinen, Johanna; Mäkelä, Satu; Mustonen, Jukka; Strandin, Tomas (Frontiers in Immunology, 2024)
Old World Orthohantaviruses cause hemorhagic fever with renal syndrome (HFRS) characterized by increased vascular permeability and acute kidney injury (AKI). Despite the systemic nature of the disease, the virus enters humans through inhalation and therefore initially encounters the immunoglobulin class A (IgA) dominated mucosal immune system. Herein, we characterized systemic IgA responses and their potential relationship to the mucosal immune activation by examining blood samples obtained from patients hospitalized due to acute Puumala orthohantavirus infection. Our findings reveal increased frequencies of putative IgA-expressing circulating mucosalassociated B1 cells and plasmablasts, as well as elevated levels of polyreactive, polymeric, virusspecific and secretory IgA in the acute stage of the disease. Importantly, the levels of circulating virus-specific and secretory IgA, as well as the putative IgA+ B1 cells, associated increased with the severity of AKI. Furthermore, circulating polymeric IgA displayed enhanced effector functions by forming stable complexes with the IgA receptor CD89 and induced pro-inflammatory neutrophil responses. These results suggest that excessive levels of circulating mucosal-like IgA might serve as a biomarker for HFRS disease progression.These results suggest that, while an efficient mucosal immune response is likely to be crucial for infection clearance, an excessive mucosal immune activation may contribute to HFRS disease progression.